1976
DOI: 10.1021/bi00647a029
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of phosphonoacetate inhibition of herpesvirus-induced DNA polymerase

Abstract: Phosphonoacetate was an effective inhibitor of both the Marek's disease herpesvirus- and the herpesvirus of turkey-induced DNA polymerase. Using the herpesvirus of turkey-induced DNA polymerase, phosphonoacetate inhibition studies for the DNA polymerization reaction and for the deoxyribonucleoside triphosphate-pyrophosphate exchange reaction were carried out. The results demonstrated that phosphonoacetate inhibited the polymerase by interacting with it at the pyrophosphate binding site to create an alternate r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
79
0
1

Year Published

1980
1980
2010
2010

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 209 publications
(84 citation statements)
references
References 21 publications
4
79
0
1
Order By: Relevance
“…PAA appears to act as a pyrophosphate analog in the polymerase active center of sensitive DNA polytial to be useful, but the currently available inhibitors merases to severely reduce the polymerization reaction are not specific. Aphidicolin, for example, inhibits all (Leinbach et al 1976). Thus, since yeast like other euthree replicative DNA polymerases, DNA pols ␣, ␦, and karyotes is relatively resistant to PAA, PAA sensitivity is ε (Burgers and Bauer 1988).…”
mentioning
confidence: 99%
“…PAA appears to act as a pyrophosphate analog in the polymerase active center of sensitive DNA polytial to be useful, but the currently available inhibitors merases to severely reduce the polymerization reaction are not specific. Aphidicolin, for example, inhibits all (Leinbach et al 1976). Thus, since yeast like other euthree replicative DNA polymerases, DNA pols ␣, ␦, and karyotes is relatively resistant to PAA, PAA sensitivity is ε (Burgers and Bauer 1988).…”
mentioning
confidence: 99%
“…Results from biochemical (e.g. Leinbach et al, 1976;Reno et al, 1978) and genetic (Honess & Watson, 1977;Chartrand et al, 1979Chartrand et al, , 1980 investigations are consistent with inhibition of the activity of the virus-coded DNA polymerase as the primary site of action of PAA on HSV replication. Phosphonoacetic acid-resistant (U) variants of HSV are readily selected during virus growth in the presence of the drug and pr determinants have been linked by both conventional genetic (Honess & Watson, 1977; and physical mapping techniques to the DNA polymerase locus of HSV.…”
Section: Introductionmentioning
confidence: 69%
“…These studies lead to the conclusion that PFA does not compete with the incoming nucleotide. On the other hand, it has been consistently found that PFA competitively inhibited the ATP-PP i exchange reaction (26,29), and PFA has been used as a pyrophosphate analog for product inhibition studies in a variety of DNA polymerases (29,30). The interaction between foscarnet and pyrophosphate is not completely straightforward, however, because high levels of resistance to foscarnet are usually not associated with high levels of resistance to PP i (14,26,28).…”
Section: Discussionmentioning
confidence: 99%